Effect of feeding betaine hydrochloride and bypass fat supplement on feed intake, milk yield and physiological parameters in lactating buffaloes during heat stress - Shankhpal, Sachin; Waghela, Chanchal; Sherasia, Pankaj; Srivastava, Ajay; Sridhar, V (Indian Journal of Dairy Science, 2019)
Present study examined the effect of feeding betaine hydrochloride (BH) and bypass fat (BF) in 24 early lactating buffaloes during May to July, 2018 in Nadiad district of Gujarat state. Buffaloes (30-35 days in milk) yielding 10-12 kg milk/d were divided into three groups of eight each based on milk yield, fat% and stage of lactation. Buffaloes in T1 group (control) were fed basal ration. In addition to basal ration, buffaloes in T2 group were fed daily 30 g BH + 100 g buffer; while buffaloes in T3 group were fed daily 30 g BH + 100 g buffer + 100 g BF for 60 days. Average thermal humidity index was 80.10 at 14:00 hr during the trial period. Study revealed that DMI improved (P=0.011) in T3 group as compared to control. Non-significant difference in milk yield was observed among the groups, however, reduction in milk yield was lower in T2 & T3 groups, as compared to control. Milk fat improved by 3.2% and 6.2% (P=0.002) in T2 and T3 groups, respectively. Rectal temperature (102.8, 102.7 vs 103.6 Â°F), respiration rate (46.0, 45.1 vs 60.1 breath/min.) and pulse rate (61.2, 58.5 vs 72.9 pulse/min.) at 14:00 hr were significantly (P<0.01) lower in buffaloes under T2 and T3 group as compared to T1 group. Average net daily income was increased by Rs. 36.02 and 47.43 in T2 and T3 group, respectively as compared to control.